Instantaneous stabilization of floating oils by surface application of natural granular materials (beach sand and limestone). Issue 1 (15th February 2015) - Boglaienko, Daria; Tansel, Berrin
Graphical abstract: Highlights: Natural granular materials can be used to capture floating oils from salt water. Limestone and sand were used to transform floating oils to oil–particle aggregates. Oil captured by aggregates was studied in relation granular material added. Oil removal efficiency increased with increasing amount of granular materials. Oil removal was not linear with the amount of granular materials applied. Abstract: When granular materials are applied to hydrophobic liquids floating over another liquid (i.e., water), particles form aggregates which can be separated from the floating phase. This concept can be used for controlling mobility of floating oils, especially after oil spills near coastal areas. The objectives of this research were to characterize oil capture efficiency and determine effectiveness of particles for converting the floating phase to a heavier phase for effective separation. Experiments were conducted with South Louisiana crude oil contaminated salt water, limestone and quartz sand. Although the oil removal efficiency increased with the increasing amount of granular material applied, it did not increase linearly. About 50% of the floating oil was removed by aggregates, regardless of the material used, when granular material to floating oil ratio was about 1 g/g. The aggregates separated had higher amounts of oil content when smaller amounts of granular materials were added.